Eksistensi Pesantren dan Deradikalisasi Pendidikan Islam di Indonesia (Menyemai Spirit Toleransi dan Pendidikan Islam Multikultural) - Huda, Mualimul (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2018)
Religious life in Indonesia is very dynamic with the emergence of various cases set to religious radicalism.. The phenomenon is not only growing at a particular community, but its existence has been developing in the form of transnational institution. Even pesantren as part of Islamic tradition of archipelago is often associated as' base or central understanding of Islam fundamental become root for growth radical movement that in the name of Islam. The radicalization of understanding at certain pesantren huts that impact on acts of radicalism in Indonesia should be laid in the context of the development of transnational Islamic movements due to the various developments of the existing world. The results of this study concluded that Islam as a universal religion of love (rahmatan lil 'alamin) which teaches education by upholding human values, respecting human rights, respecting cultural and cultural diversity, craving peace, justice, tolerance and a balanced attitude, and other noble manifestations. Dogmatic groups that justify acts of violence in the name of religion have reduced and injured the teachings of rahmatan lil 'alamin. Islamic education (Pesantren) that teaches hatred against different opinions and beliefs is not ideal for the continuity of diversity and diversity in Indonesia. Pesantrens infiltrated by radicalization need to be reoriented in a direction compatible with the Islamic spirit that teaches mutual respect and brotherhood. A number of values that are taught are tolerant, moderate, togetherness, equality, mutual respect and degrees of Islamic multicultural education